Z-oo9 - Guided bone regeneration associated hydroxyapatite ceramic (Endobone®) and rhBMP-2 (Infuse ®) - Puttini, IO; Ferreira, S; Santos, P; Magro Filho, O; Garcia Junior, IR (ARCHIVES OF HEALTH INVESTIGATION, 2013)
The autogenous bone is considered the ideal grafting material for sinus lifting, although their exploration causes severe discomfort to the patient. Many approaches have been made to obtain the elevation of the sinus with preexisting tissue. However, due to the suitability of such tissue, additional materials were needed. Alternatively, biomaterials are used. In this case, the efficiency of utilization of bone morphogenetic bovine protein (rhBMP-2) to increase the floor of the maxillary sinus was observed. A 52 years old patient requiring oral rehabilitation showed up in surgery clinic FOA / UNESP. At initial images exams was possible to observe large pneumatization of the maxillary sinus. It was proposed then the graft of the maxillary sinus with hydroxyapatite ceramic (Endobone ®) associated with bone morphogenetic protein (Infuse ®) by Caldwell Luc access. The procedure was performed under local anesthesia where after the approach of the maxillary sinus the sinus membrane was elevated to fill it out. The BMP was incorporated into the collagen sponge and to the Endobone ®. The postoperative X-ray shows increased radiopacity inside the maxillary sinus suggestive of gain of mineralization. Therefore, this material can provide an alternative to autogenous bone grafts, preventing the discomfort of the patient. igorputtini@gmail.com